Validation of the Arabic version of the Mental Health Literacy Scale (MHLS) in three Arab samples - Fareeda Abo-Rass; Ora Nakash; Sarah Abu-Kaf; Bizu Gelaye; Hanan AboJabel; Anwar Khatib (PLoS ONE, 2025)
Mental Health Literacy (MHL) is pivotal for understanding and addressing mental disorders, often assessed using the comprehensive Mental Health Literacy Scale (MHLS) across six dimensions and 35 items. However, research on MHL within Arab populations is not just scarce, but alarmingly so, indicating a significant gap in knowledge regarding MHL in this demographic. This study aimed to fill this gap by adapting the MHLS into Arabic and evaluating its psychometric properties among three distinct Arabic-speaking groups: adolescents, students, and the general public. Data were collected using the translated MHLS, the General Health Questionnaire, and sociodemographic measures, employing a cross-sectional design. Validation procedures were conducted, including exploratory factor analysis, reliability testing, and face validity assessment. Construct validity was assessed using Pearson correlation analysis and t-tests. The validation process yielded three modified versions of the MHLS in Arabic: MHLS-Arabic-Adolescents (31 items, 5 factors), MHLS-Arabic-Students (30 items, 6 factors), and MHLS-Arabic-General Public (33 items, 5 factors). These tools demonstrated robust construct validity and high-reliability coefficients and stood as a testament to their adaptability and potential for use in diverse Arabic-speaking populations. This study suggests the nuanced nature of MHL and points to the importance of micro-context-specific validation. Providing three reliable MHLS Arabic versions could facilitate research on MHL among Arabic-speaking populations worldwide, potentially leading to tailored intervention initiatives that aim to enhance mental health outcomes and ensure equitable access to services within Arab communities globally.